The translator of desires - Ibn al-ʻArabī, 1165-1240 (Lockert library of poetry in translation., 2021)
"A complete facing-page translation of the Tarjuman, which consists of sixty-one poems composed between 1202 and 1215 CE and published in 1215 at the earliest. The first word of the title can refer to a translator, interpreter, or biographer, on the one hand, and to a translation, interpretation, or biography on the other"--